A FRET–ICT dual-quenching fluorescent probe with large off–on response for H2S: synthesis, spectra and bioimaging. Issue 35 (2nd April 2015) - Zhang, Changyu; Wei, Lv; Wei, Chao; Zhang, Jie; Wang, Runyu; Xi, Zhen; Yi, Long
Abstract : A FRET–ICT dual-quenching fluorescent probe with significant off–on response toward H2 S is rationally designed and prepared for imaging of H2 S in living cells. Abstract : A FRET–ICT dual-quenching probe with large off–on fluorescent response upon H2 S treatment is reported. The probe can be used for bioimaging of endogenous H2 S in living cells.